ЕКОНОМІЧНІ ІНТЕРЕСИ ДЕРЖАВИ ЯК ОБ’ЄКТ ЗАХИСТУ ПРОКУРОРОМ В АДМІНІСТРАТИВНОМУ СУДОЧИНСТВІ УКРАЇНИ - Sybirtseva, E.Yu. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2013)
The paper determines the grounds for representation of the state’s interests by the public prosecutor in administrative proceedings of Ukraine. Based on the analysis of researches into the modern legal science, the concept “economic interest of the state” was defined. REFERENCES: